Innovative approaches to analysis of parameters of shooting skills of biathletes using wireless optical sensor SCATT MX-W2 - Zagursky, N. S.; Romanova, Y. S. (Theory and Practice of Physical Culture, 2021)
The article presents the data of testing the shooting skills of biathletes of the Russian national team, obtained with the help of the SCATT MX-W2 wireless optical sensor and the analysis program. The analysis of the shooting parameters obtained using the SCATT MX-W2 wireless optical sensor makes it possible to develop an algorithm for managing the improvement of the shooting training of biathletes when firing ammunition. The examples of individual analysis of graphic and digital parameters of the technique of performing a series of shots are shown, which makes it possible to identify errors, develop individual programs for shooting training and recommending ways to eliminate the identified deficiencies.